Current Data on Risk Factor Estimates Does Not Explain the Difference in Rates of Melanoma between Hispanics and Non-Hispanic Whites - Sonia Kamath; Kimberly A. Miller; Myles G. Cockburn (Journal of Skin Cancer)
United States Hispanics have seven times lower melanoma incidence rates than non-Hispanic whites (NHW). It is unclear whether this difference can be explained solely by phenotypic risk factors, like darker skin, or whether modifiable risk factors, like sun exposure, also play a role. The purpose of this paper is to summarize what is currently known about melanoma risk factors among Hispanics and NHWs, and whether or not those differences could explain the difference in melanoma incidence. Through literature review, relative risks and prevalence of melanoma risk factors in Hispanics and NHWs were identified and used to calculate the expected rate in Hispanics and rate ratio compared to NHWs. We found that melanoma risk factors either have similar frequency in Hispanics and NHWs (e.g., many large nevi) or are less frequent in Hispanics but do not explain a high proportion of disease variation (e.g., red hair). Considering current knowledge of risk factor prevalence, we found that melanoma incidence rates in the two groups should actually be similar. Sun exposure behavior among Hispanics may contribute to the explanation for the 7-fold difference in melanoma rates. Currently, limited data exist on sun exposure behavior among Hispanics, but possibilities for improving primary prevention by further studying these practices are substantial.